2018
DOI: 10.1021/acsami.8b17273
|View full text |Cite|
|
Sign up to set email alerts
|

Atomistic Mechanisms of Mg Insertion Reactions in Group XIV Anodes for Mg-Ion Batteries

Abstract: Magnesium (Mg) metal has been widely explored as an anode material for Mg-ion batteries (MIBs) owing to its large specific capacity and dendrite-free operation. However critical challenges, such as the formation of passivation layers during battery operation and anode-electrolyte-cathode incompatibilities, limit the practical application of Mg-metal anodes for MIBs. Motivated by the promise of group XIV elements (namely Si, Ge and Sn) as anodes for lithium-and sodium-ion batteries, here we conduct systematic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 72 publications
3
25
4
Order By: Relevance
“…Alloying materials have shown great promise as anode materials for AMIBs (Figure 8) due to their high energy density and low voltage operation. [180,[277][278][279][280][281][282][283][284][285][286][287] The modeling of the alloying anodes is typically different to the modeling of the insertion/ intercalation-type materials. These anode materials typically undergo an electrochemical alloying process via the reversible reaction AM B e AM B x y x…”
Section: Alloying Anode Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alloying materials have shown great promise as anode materials for AMIBs (Figure 8) due to their high energy density and low voltage operation. [180,[277][278][279][280][281][282][283][284][285][286][287] The modeling of the alloying anodes is typically different to the modeling of the insertion/ intercalation-type materials. These anode materials typically undergo an electrochemical alloying process via the reversible reaction AM B e AM B x y x…”
Section: Alloying Anode Materialsmentioning
confidence: 99%
“…Alloying materials have shown great promise as anode materials for AMIBs ( Figure 8 ) due to their high energy density and low voltage operation. [ 180,277–287 ] The modeling of the alloying anodes is typically different to the modeling of the insertion/intercalation‐type materials. These anode materials typically undergo an electrochemical alloying process via the reversible reaction xAM+ + ynormalB + xe AMxBy$x{\rm{A}}{{\rm{M}}^ + }\, + \,y{\rm{B}}\, + \,x{{\rm{e}}^ - } \rightleftharpoons \,{\rm{A}}{{\rm{M}}_x}{{\rm{B}}_y}$, where AM + is the alkali metal ion, and B the alloying anode material (Figure 8).…”
Section: Alloying Anode Materialsmentioning
confidence: 99%
“…Long term cycling performance of Si‐based anode materials however is mainly limited by large structural volume change and swelling event, along with particle pulverization and the mechanical and electrical disintegration during repeated cycling. Similar remark will pertain to the Si of a Mg cell that undergoes a large volume change (216 %) upon magnesiation and demagnesiation 10,31 …”
Section: Introductionmentioning
confidence: 83%
“…Similar remark will pertain to the Si of a Mg cell that undergoes a large volume change (216 %) upon magnesiation and demagnesiation. 10,31 A basic understanding of the electrochemical properties of a new electrode material and the electrodeelectrolyte interfacial reaction behavior, and the clarification of the reason for low electrochemical activity is obtainable through the studies of film model electrodes. Film model electrode deposited on electronically conductive substrate comprises no complications from carbon and polymeric binder additives that are necessary in bulk porous electrodes, and can provide high-quality spectroscopic signals and a precise characterization of the surface composition, which gives a clear insight into electrode-electrolyte interfacial processes and reaction mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The Ga‐doped Ge anodes show obviously reduced insertion and migration barriers, which exhibit a similar behavior of Mg insertion into Al‐doped Si electrodes. [ 126 ] Based on first‐principle calculations, Wang et al [ 128 ] have shown that amorphous Ge can be potentially effective as an anode material for Mg‐alloy anodes in practical applications related to MIBs. Amorphous Mg x Ge phase was found to be formed through a partial breaking of the Ge crystalline network, replaced by MgGe bonds, which are weaker than GeGe bonds.…”
Section: Group Iva Element (Si Ge Sn and Pb) Alloy Anodesmentioning
confidence: 99%